A Comparative Study of Physical Fitness Levels Among Junior High School Students in Rural and Urban Areas - M. Ilham Ramadhan Suarlam; Muh Adnan Hudain; Jamaluddin Jamaluddin (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Physical fitness is a fundamental indicator of adolescent health, yet geographic disparities often create significant gaps in fitness achievement. This study aims to analyze and compare the physical fitness levels of junior high school students in rural and urban areas within the Polewali Mandar Regency. Using a quantitative descriptive approach with a comparative survey design, the study sampled 60 students from four schools: Junior High School 1 Polewali, Junior High School 1 Anreapi, Junior High School 1 Wonomulyo, and Junior High School 4 Wonomulyo. Data were collected using the Indonesian Student Fitness Test (TKSI) Phase D, covering hand-eye coordination, sit-ups, standing broad jumps, T-tests, and Bleep tests. The findings reveal a significant difference in physical fitness between the two groups. Although both cohorts fall within the "moderate" category, rural students demonstrated superior fitness with a mean score of 17.43, compared to 15.90 for urban students. This research highlights how geographic environments influence physical activity, suggesting that rural settings may naturally facilitate higher physical engagement. These results serve as a critical reference for educators and policymakers to design targeted fitness interventions, particularly for urban school settings, to bridge the fitness gap among adolescents.